Kajian Biblika Terhadap Teks 1 Korintus 10:6-10 - Nehemia Nome; Filmon Berek; Yunus Selan; Charisal B.S. Manu; Adi Putra (JURNAL LUXNOS, 2022)
Abstract: This research is about biblical study of the text of 1 Corinthians 10:6-10. Where this research seeks to find out what meaning is contained in the text or passage. By using an approach approach, especially library research, the following results and conclusions are obtained. In sections 10:1-10 Key as clues referring to the stories in the Book of Exodus (cloud, sea, manna, golden calf), through the LXX. While the stories that refer to the book of Numbers (rocks, Baal Peor, snakes, murmurs in the punishment of the children of Korah) come from the Judaism tradition. It is possible that when Paul wrote his letter, he only had one copy of the LXX version of the Book of Exodus, but for Numbers he would have to rethink his studies first. Abstrak: Penelitian ini tentang kajian biblika terhadap teks 1 Korintus 10:6-10. Di mana penelitian ini berusaha mencari tahu makna apa yang terkandung di dalam teks atau perikop tersebut. Dengan menggunakan pendekatan kualitatif, khususnya kajian pustaka, maka diperoleh hasil dan kesimpulan penelitian berikut ini. Pada bagian 10:1-10 disimpulkan sebagai petunjuk-petunjuk yang merujuk kepada cerita-cerita dalam Kitab Keluaran (awan, laut, manna, anak lembu emas), melalui LXX. Sedangkan cerita-cerita yang merujuk kepada kitab Bilangan (batu karang, Baal Peor, ular, sungut-sungut dalam hukuman bani Korah) berasal dari tradisi Yudaisme. Mungkin saja ketika Paulus menulis suratnya, dia hanya memiliki satu eksemplar Kitab Keluaran versi LXX, tetapi untuk Bilangan ia harus mengingat kembali studinya dahulu.